Integrated assessment of environmental suitability and water-energy conflict for optimizing solar energy in Northwest China's desert regions - Weike Zhao; Zhangxinyue Zhao; Wenjuan Hou; Dezheng Jiang; Kaijin Zhang; Xueliang Zhang (Environmental and Sustainability Indicators)
This study evaluates the environmental suitability and water resource impact of photovoltaic (PV) and concentrated solar power (CSP) systems in the desert regions of Northwest China. A Multi-Criteria Decision Analysis (MCDA) approach is employed, integrating seven key indicators that encompass climate, geography, and location perspectives. Methods such as AHP, CRITIC, CVM, IWC, and EWM are integrated into the MCDA system, with sensitivity analysis conducted to ensure the robustness of weight coefficients. Additionally, the study employs the Water Resource Pressure (WRP) index and spatial Gini coefficient to quantify the Water-Energy conflict. The findings indicate that the Tengger and Kumtag Deserts exhibit higher environmental suitability, lower water resource pressure, and favorable spatial equilibrium, making them optimal for PV and CSP development. In contrast, the Ulan Buh, Badain Jaran, and Qaidam Deserts face significant water resource pressures, necessitating careful planning to avoid ecological impacts. This study introduces a comprehensive framework that combines suitability assessments with water resource evaluations at a fine spatial scale of 0.25-degree grids. The proposed “Water-Electricity-Road” network framework addresses water scarcity and infrastructure accessibility, thereby optimizing solar energy utilization in desert regions. These insights offer valuable guidance for sustainable solar energy planning in arid regions globally.